Community Response to Settlement Relocation After Liquefaction in Petobo Village - Elly Kustiana; Iwan Alim Saputra; Amalia Novarita (Universitas Sebelas Maret, 2020)
The liquefaction disaster caused loss of compact settlements in Petobo, the attention of the government to relocate community settlements to permanent residences. The purpose of this study was to knowing the response community of relocated settlement post liquefaction disaster in petobo. This study of type a qualitative description for purposive sampling. The general results analysis studies that 25 (83,33 %) to knowing the response community and 30 (100 %) the community response agree with for plan the relocated settlement’s post liquefaction disaster in Petobo, Palu City. For 28 (98,33 %) the community response disagrees with the government policy due to move the settlements another place. Generally, the community hope if the relocated settlements to do as soon as possible and still in petobo. Disagree process due too the community will not leave from petobo because they are authentic community in petobo.